IN VITRO SCREENING OF HEAVY METAL TOLERANT PHOSPHATE SOLUBILIZING PLANT GROWTH PROMOTING ISOLATES - M. CHANDINI PATNAIK, NISSI PAUL. M, S. TRIVENI, P. C LATHA and (The Journal of Research, PJTSAU, 2019)
The present study was conducted to isolate promising heavy metal tolerant bacteria from various industrial polluted areas of Hyderabad, India and to test for their plant growth promoting characteristics. Eight Pseudomonas strains isolated were tested for their maximum tolerance to heavy metals (Ni, Cd, Co, Pb) by supplementing their respective salts in different concentrations (0, 25, 50, 100, 150 and 200 mgl-1) to King’s B agar. Among all strains AfS-8,AfS-8, UpW-13 and SfW-14 were able to tolerate upto 100 mg l-1 concentration of heavy metals. All the isolates were also screened for various biochemical traits like mineral (P, K) solubilisation, HCN production, IAA production, Siderophore production, EPS production ACC deaminase activity.